Pemberian Senam Aerobik untuk Mencegah Low Back Pain pada Siswa SD Kandang Panjang 10 Kota Pekalongan - Muhammad fadli ramadhani; Albani, Rizky Azriel; Hidayat, Azam Syarif; syafwana, Syafig Trisna; Saputra, Fikki Arifani (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
Student physical fitness is an important aspect that can increase mobility in achieving maximum academic achievement. Efforts to improve the physical fitness of students can be through various physical activities, one of which is gymnastic activities. The purpose of this community service is to provide scientific provision in preventing low back pain in students of SD Kandang Panjang 10, Pekalongan city. The method used in this service uses the demonstration method. The results of the implementation of community service activities are expected to be able to provide knowledge to elementary school students at Panjang 10 Pekalongan city and can prevent low back pain